\[\boxed{\text{217\ (217).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ \left( - a^{5} \right)^{2} = a^{10}\]
\[2)\ \left( - a^{3} \right)^{3} = - a^{9}\]
\[3)\ \left( - a^{4} \right)^{7} \cdot \left( - a^{2} \right)^{6} =\]
\[= - a^{28} \cdot a^{12} = - a^{40}\]
\[\boxed{\text{217.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[= 1,5\]
\[Получим\ из\ левой\ части\ \]
\[равенства\ правую:\]
\[= 1,5.\]
\[1,5 = 1,5\]
\[\Longrightarrow тождество\ доказано.\]
\[2)\ 7a \cdot (3b + 4c) - 3a \cdot \left( b + \frac{1}{3}c \right) =\]
\[= 9a \cdot (2b + 3c)\]
\[Получим\ из\ левой\ части\ \]
\[равенства\ правую:\]
\[= 9a \cdot (2b + 3c)\]
\[9a \cdot (2b + 3c) = 9a \cdot (2b + 3c)\]
\[\Longrightarrow тождество\ доказано.\ \]